Relevance of PSGL-1 Expression in B Cell Development and Activation - González-Tajuelo, Rafael; González-Sánchez, Elena; Silván, Javier; Muñoz-Callejas, Antonio; Vicente-Rabaneda, Esther; García-Pérez, Javier; Castañeda, Santos; Urzainqui, Ana (Frontiers in Immunology, 2020)
PSGL-1 is expressed in all plasma cells but only in a small percentage of circulating B cells. Patients with systemic sclerosis (SSc) show reduced expression of PSGL-1 in B cells and increased prevalence of pulmonary arterial hypertension. PSGL-1 deficiency leads to a SSc-like syndrome and SSc-associated pulmonary hypertension in female mice. In this work, the expression of PSGL-1 was assessed during murine B cell development in the bone marrow and in several peripheral and spleen B cell subsets. The impact of PSGL-1 absence on B cell biology was also evaluated. Interestingly, the percentage of PSGL-1 expressing cells and PSGL-1 expression levels decreased in the transition from common lymphoid progenitors to immature B cells. PSGL-1−/− mice showed reduced frequencies of peripheral B cells and reduced B cell lineage-committed precursors in the bone marrow. In the spleen of WT mice, the highest percentages of PSGL-1+ populations were shown by Breg (90%), B1a (34.7%) and B1b (19.1%), while only 2.5-8% of B2 cells expressed PSGL-1; however, within B2 cells, the class-switched subsets showed the highest percentages of PSGL-1+ cells. Interestingly, PSGL-1-/- mice had increased IgG+ and IgD+ subsets and decreased IgA+ population. Of note, the percentage of PSGL-1+ cells was increased in all the B cell subclasses studied in peritoneal fluid. Furthermore, PSGL-1 engagement during in vitro activation with anti-IgM and anti-CD40 antibodies of human peripheral B cells, blocked IL-10 expression by activated human B cells. Remarkably, PSGL-1 expression in circulating plasma cells was reduced in pulmonary arterial hypertension patients. In summary, although the expression of PSGL-1 in mature B cells is low, the lack of PSGL-1 compromises normal B cell development and it may also play a role in the maturation and activation of peripheral naïve B cells.